1962
DOI: 10.1017/s0022029900017799
|View full text |Cite
|
Sign up to set email alerts
|

Quelques facteurs de variation de la teneur en calcium des laits de vaches

Abstract: SummaryA study was made of the effect of various factors which may influence the calcium content of milk. The basic data consisted of the calcium content of 20840 samples of individual milks, taken once a month, during the course of 2300 lactations of Montbeliarde cows. For each lactation, a weighted average figure for the calcium concentration was calculated, taking into account the milk quantities recorded on each sampling day. The calcium content has been expressed in g/kg of milk.The stage of lactation cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Of the four elements to be discussed in this paper, the content of potassium in milk decreases and that of sodium increases as stage of lactation increases (6, t4). Calcium (1,9) and magnesium contents (9) decline during the early stages of lactation and increase in late lactation. Vanschoubroek (16) suggested that these seasonal or lactational changes in the concentration of minerals in milk also correspond to major dietary changes such as the rotation of stall feeding and pasture grazing.…”
Section: Introductionmentioning
confidence: 99%
“…Of the four elements to be discussed in this paper, the content of potassium in milk decreases and that of sodium increases as stage of lactation increases (6, t4). Calcium (1,9) and magnesium contents (9) decline during the early stages of lactation and increase in late lactation. Vanschoubroek (16) suggested that these seasonal or lactational changes in the concentration of minerals in milk also correspond to major dietary changes such as the rotation of stall feeding and pasture grazing.…”
Section: Introductionmentioning
confidence: 99%
“…Auriol and Mocquot () reported that levels of total calcium decreased during the first month of lactation and increased significantly during the last 3 months. Kamal et al .…”
Section: Physiological Factors Affecting the Composition Of Bovine Milkmentioning
confidence: 99%